Côlon irritable et paramètres influençant. Enquête sur des cas hospitaliers au niveau de la wilaya de Mostaganem - KAHLOUCH, Salima; KETROUCI, Nassira (My University, 2018)
In this work, we have studied the effect of some parameters on the prevalence of irritable bowel syndrome (IBS). As well as the cases reached and which have been archived at Guevara hospital of Mostaganem. We performed an analysis of the data on all patients with IBS who reside only in Mostaganem’s areas. The survey on the associated dietetics is carried out on 40 patients studied over a period of 3 months between February and April 2018. The survey on the importance of food has shown that the most consumed foods in patients at breakfast are mainly; dairy products (82.5%), coffee (55%), and sweets (45%). Lunch and dinner meals included meats (77.5%), pasta (77.5%), and beverages (67.5%). Regarding the symptoms of IBS, their severity varies from one person to another since there are a multiple factors that influence as; physiological state, age, weight etc. It was reported that females (55%) are more affected than males (45%). In subjects whose age is between 15 and 34 years. Mostaganem center region took the first place (42.5%) among all the other regions studied; in terms of attaining this pathology
Keywords: Côlon irritable (SCI); Enquête; Repas; Prévalence; Irritable bowel syndrome (ICS); Survey; Meals; Prevalence.